Evaluating cool‐season grass species as potential perennial groundcover for maize production. (17th June 2022) - Chen, Allen; Fei, Shui‐zhang; Lenssen, Andrew William; Moore, Kenneth J.
Abstract: Removal of crop residue poses negative consequences for soil health, nutrient leaching, and runoff. Perennial groundcovers (PGC) provide a method of maintaining soil health while allowing the sustainable intensification of maize ( Zea mays L.) systems for biofuel production by providing groundcover for several years. However, previous studies have only evaluated a few varieties of PGC. We conducted a 2‐yr study to evaluate the compatibility of cool‐season turfgrass PGCs under maize. Maize was interplanted into 20 accessions of Kentucky bluegrass ( Poa pratensis L.), Sandberg bluegrass ( Poa secunda J. Presl), and red fescue ( Festuca rubra L.) in a randomized complete block design in Boone, IA. Data on maize grain yield, maize grain quality, and ground coverage of PGC were collected. There were no differences in maize grain yield across species in 2017. In 2018, maize grain yield under red fescue was 1.0, 1.8, and 2.1 Mg ha –1 less than Kentucky bluegrass, Sandberg bluegrass, or the no‐grass control, respectively. Maize under red fescue produced 2.3, 4.8, and 3.9 g kg –1 more protein than Kentucky bluegrass, Sandberg bluegrass, and the no‐grass control, but produced 878 L ha –1 and 758 L ha –1 less ethanol than the no‐grass control and Sandberg bluegrass, respectively. In both years, Kentucky bluegrass groundcover declined approximately 22%, while Sandberg bluegrass groundcover remained below 10%. Red fescue maintained groundcover over 22% in 2017 and 34% in 2018. These results indicate that maize under Kentucky bluegrass and Sandberg bluegrass can perform similarly to conventional maize. Core Ideas: Perennial groundcovers can provide natural resource benefits in maize production. As species, Kentucky bluegrass and Sandberg bluegrass can be compatible with maize. Maize grown with certain accessions can maintain or increase grain yield. Differences were observed in Kentucky bluegrass and Sandberg bluegrass accessions.